The relation between postpartum depression with total serum cholesterol changes before and after child birth - shahnaz Golyan Tehrani; mehrnaze Geranmayeh; ozra Cheraghi; abas mehran (Tehran University of Medical Sciences, 2007)
Background & Aim: Postpartum depression is a severe and pervasive sadness with labile mood that affect 8-15% women after delivery. It can negatively impress mother-infant bonding. There are a lot of factors which make women vulnerable to postpartum depression so that controlling them can prevent from the postpartum depression incidence. Several researches have shown an association between serum cholesterol reduction and depression. The aim of present study is to determine relation between postpartum depression with total serum cholesterol changes before and after child birth in Lahijanian women in years 2006-2007. Methods & Materials: This research sought a descriptive-analytical design. Samples consisted of healthy Primigravidia women (101 persons) with normal labor, normal delivery at term, married, and a medium to high socio-educational level, without history of a depressive disorder, and metabolic disorders or hyperlipidemia. The excluded were the women with maternal or fetal complication before delivery, having problem with accepting infant gender, fetal death and being depressed during pregnancy. All women were visited in two stages: 3 weeks before the expected delivery and also 6 weeks after delivery. On both visits the Beck depression inventory and serum cholesterol registration questionnaire were completed. Data were collected using a questionnaire which had three sections: demographic characteristics, the Beck depression inventory and laboratory tests. Data were analysed using descriptive and inferential statistics (Spearman correlation coefficient and t-test) by SPSS computer software. Results: Findings indicated that serum cholesterol declined considerably in the postpartum period, also it was shown that there was a significant correlation between reduced serum cholesterol and postpartum depression (r=-0.331, P<0.001). Conclusion: Serum cholesterol reduction has a relation with postpartum depression.